Gestión administrativa del cyber "Andinacom.Net" del cantón Montalvo, periodo 2022. - Gallegos Medrano, Jessica Carmelina (2023)
The present case study was carried out Cyber "Andinanet.Com" of the Montalvo canton, the main objective is to analyze the Administrative Management processes that influence Cyber andinanet.com to improve its quality and service, this work aims to know the administrative management to increase sales in the cyber, the reason for this research topic to increase sales, and promote new alternatives to improve the management of the company. Today, administrative management in a company is key and serves as the basis for the execution and potentialization of tasks to meet the objectives set and contribute to its survival and growth. The constant search for an administrative management that allows to give a better image to the company, improve the administrative, productive processes, among others, that are developed within it, this article focuses on the organization in order to improve the processes for their development and well-being, whose objective was to determine the situation in which the company is located and to show if the administrative management affects productivity, in order to meet the stated objective. The quantitative and descriptive methodology used, the support of the theoretical base is based on the variables, results were obtained with reference to the discussion with the instruments that were applied to reach the results, addressing exhaustive issues contributing to the consolidation of the same that culminates in issuing conclusions.